THE IMPLEMENTATION OF FIVE RIGHTS MEDICATION ADMINISTRATION BY NURSES AT A PRIVATE HOSPITAL IN WESTERN INDONESIA - Evani Fransiska; Inriana Nadia M Harefa; Nani Rejeki S.F Lumbangaol; Ineke Patrisia; Mega Tri Anggraini (Universitas Pelita Harapan, 2022)
This study aimed to observe how nurses implement the five rights. The initial survey of ten nurses in an inpatient department showed 50% did not adhere to hospital standard operating procedure when administrating the drugs to patients, and majority had never performed five rights check before, which harmful to patients. This study used a quantitative descriptive method. The sample for this study was a purposive sampling, researchers have observed 33 nurses from three departements including Emergency, Inpatient, and Intensive Care Unit departements at one private hospital in Indonesia. A standard operating procedure for hospital was used as an instrument. Researchers observed nurses without letting them knoe when the day observing would begin. 84.85% of them have worked more than a year in the hospital. 18.18% of nurses did not check the right patient, 12.12% did not check the right drug, 18.18% did not check the right dose, 9.09% did not give the medication at the right time, and 3.03% did not give the medicine with the right route. Most nurses followed hospital standard operating procedures by implementing all five rights checjs before administrating the medications to patients. For the hospital management, it is suggested to facilitate the nurses with more training or workshop about the implementation of five rights or the role of nurses as medication administrators.